Implementation of Social Security for Workers in The Informal Sector: A Study of Bukan Penerima Upah (BPU) at BPJS Ketenagakerjaan Duri - Jaksana Arifin; Muammar Alkadafi (Journal of Social and Policy Issues, 2026)
This study aims to analyze the implementation of the BPJS Employment program for non-wage workers (BPU) in Duri City and to identify the factors influencing its low participation rate. The research employs a qualitative descriptive approach, using in-depth interviews, observation, and documentation as data collection techniques. Informants were selected through purposive and snowball sampling, involving one BPJS Employment officer and fifteen informal workers. Data were analyzed using Miles and Huberman’s interactive model, while data validity was ensured through triangulation and member checking. The findings indicate that the implementation of the BPU program in Duri City has not been optimal, as only 34.07 percent of informal workers are registered as active participants. Key obstacles include limited social security literacy, unstable income, weak understanding of program benefits, and low prioritization of contribution payments among workers. From an institutional perspective, limited outreach, a shortage of Perisai agents, and minimal involvement of the local government further constrain effective implementation. Using Grindle’s policy implementation framework, the study reveals barriers in both policy content and implementation context. The study concludes that improving BPU participation requires targeted socialization, strengthening institutional capacity, increasing local government support, and adopting more flexible contribution mechanisms to ensure more inclusive social protection for informal workers.